Strategies of Pr-Education and Digital Communications in Russia And Kazakhstan (Herald of Journalism, 2019)
The paper presents results of comparative research in the field of PR-education development in Russia and Kazakhstan. After the disintegration of the USSR, the paths of education development in former soviet republics divided. However, there are still many similarities due to the inter-government cooperation and integration projects such as the Eurasia Economic Union. The study aims to understand how PR-education in Russia and Kazakhstan is developing. In particular, the study compares BA and MA education programs comparing courses in common and not in common. This project uses both quantitative and qualitative data collection tools but is rooted in a qualitative that recognizes the importance of locating the research within a particular social, cultural, and historicalcontext. The authors place an emphasis on the competences in the sphere of digital public relations, assuming that skills in information technologies and digital literacy are crucial for success in the future. In order to understand dynamics of PR-education development, the authors compare statistics on student submission to the institutions of the higher education both in Russia and Kazakhstan. The numbers show that there is a big demand in PR-education in terms of students submitted and in terms of competition. In order to indicate what digital skills is needed a survey method is applied. The authors have conducted a survey with 60 BA and MA students. The survey shows that students consider their decision to become a PR-specialists as ‘strategically right’, but the opinion on digital literacy was ontroversial.epistemological position
Keywords: PR-education, information technologies, digital literacy, Russia, Kazakhstan.